2017
DOI: 10.1007/s00402-017-2749-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of proximal humeral fractures by the Ilizarov external fixator

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The current study showed the efficacy of the Ilizarov external fixator in restoring huge bone defects with a mean bone loss of 10.67 cm. Further, the frame provided adequate mechanical stability, reduced complications associated with free vascular fibular graft transfer, and overcame persistent infection 18,19. However, there were a few limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study showed the efficacy of the Ilizarov external fixator in restoring huge bone defects with a mean bone loss of 10.67 cm. Further, the frame provided adequate mechanical stability, reduced complications associated with free vascular fibular graft transfer, and overcame persistent infection 18,19. However, there were a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the frame provided adequate mechanical stability, reduced complications associated with free vascular fibular graft transfer, and overcame persistent infection. 18,19 However, there were a few limitations. First, the number of cases was small because of the nature and the specific character of the causative trauma.…”
Section: Case Presentation: Patient Numbermentioning
confidence: 99%
“…These patients were evaluated monthly after the operation, every 2 to 3 months after fracture union, and every 6 months 1 year later. At the final follow-up, the functional recovery was assessed using Neer’s criteria and the visual analog score (VAS) (0 = very satisfied, 10 = no satisfaction) [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Functional outcomes were assessed at the final follow up in accordance with Neer's criteria, which included pain (none to totally disabled), function (strength, reach, and stability), ROM (flexion, abduction, extension, external rotation, and internal rotation), and anatomy (rotation, angulation, joint congruity, retracted tuberosities, metal failure, myositis, nonunion, and avascular necrosis) [10]. The degree of patient satisfaction was evaluated using the visual analog score (VAS) (0 = very satisfied, 10 = no satisfaction) at the final follow up [11]. Postoperative axillary nerve function was noted while examining the sensory territories of the axillary nerve and testing the weakness or 6 atrophy of the anterior deltoid muscle.…”
Section: Postoperative Evaluation and Managementmentioning
confidence: 99%